Determination the Value Evapotranspiration and crop coefficient of oil palm tenera Variety (Elaies guenensis Jack) - Ade Rahmi Alhas; Ainun Rohanah; Sumono Sumono (Universitas Sumatera Utara, 2016)
Considering that the oil palm plants consume a lot of water, it is needed more assessment of the magnitude of the rate of evapotraspiration especially oil palm plantations, and in the initial value stages the process can begin from nursery. The value of crop evapotranspiration can be determined based on the value of potential evaporation and oil palm crop coefficients for each growth period. This study is aimed to determine the evapotranspiration value and crop coefficients of4 months old tenera seeds.Evapotranspiration value of oil palm plantations in the initial period of plant research was 0.9 mm/day and the final period of the plant was 0.98 mm/day. The amount of evaporation in the initial period of the study was 1.98 mm/day and in the final period was 1.93 mm/day. The study shows that oil palm crop coefficient in the initial period was 0.47 and in the final period was 0.5. Keywords : Evapotranspiration, Crop coefficient, potential evaporation, oil palm Plant